Pelatihan Pembuatan Konten Kreatif Sosial Media Bagi Usaha Mikro Kecil Menengah Sidayu Gresik - Akhmad Wasiur Rizqi; Moh Nurudddin (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
training for creating creative content and social media with the object of service aimed at MSME business actors who are members of the Sidayu sub-district MSME association located in Mriyunan Village, Sidayu District, Gresik Regency. This community service is a form of campus participation, especially the Muhammadiyah Gresik Industrial Engineering department, in increasing the capabilities of local resources, namely MSME businesses. The purpose of Community Service itself is to increase insight and knowledge for MSME actors so that the products produced can be well documented and can be recognized by many people through interesting content and social media. So that it is hoped that in the future it can make a positive contribution through increasing selling prices and product competitiveness.